Collaborative Governance dalam pengembangan wisata Telaga Sewu di Desa Duren Sewu Kecamatan Pandaan Kabupaten Pasuruan - abror, daim (Jurnal Administrative Reform, 2023)
This research describes, analyzes and interprets collaborative governance in the form of a partnership pattern between the Village Government, the Private Sector and the Community in the development of Telaga Sewu Tourism in Duren Sewu Village, Pandaan District, Pasuruan Regency. The research method used is a qualitative method with a case study approach. The results of the research show that the basis or reason for the partnership between the Village Government, the Private sector and the Community in developing Telaga Sewu Tourism in Duren Sewu Village is political reasons, all parties entered into a partnership based on the interest of gaining profits. The village government can improve the realization of a democratic government, while the private sector can increase income and the community can increase family income or economy. Then there are economic reasons, where partnerships are implemented to improve the welfare of the Duren Sewu community, reduce inequality and poverty and increase income. Meanwhile, for administrative reasons, the village government entered into a partnership because it was constrained by a lack of budget for developing Telaga Sewu tourism, while the private sector entered into a partnership because they did not have complete equipment and recruited people as employees at Telaga Sewu Tourism due to a lack of natural resources. Meanwhile, the partnership pattern between the village government, the private sector and the community in developing Telaga Sewu tourism in Duren Sewu Village is more inclined towards a mutualistic partnership pattern.